2020
DOI: 10.3390/genes11091041
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota between Environment and Genetic Background in Familial Mediterranean Fever (FMF)

Abstract: The gastrointestinal tract hosts the natural reservoir of microbiota since birth. The microbiota includes various bacteria that establish a progressively mutual relationship with the host. Of note, the composition of gut microbiota is rather individual-specific and, normally, depends on both the host genotype and environmental factors. The study of the bacterial profile in the gut demonstrates that dominant and minor phyla are present in the gastrointestinal tract with bacterial density gradually increasing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 188 publications
(254 reference statements)
0
14
0
Order By: Relevance
“…Studies have demonstrated that gut microbiota plays a certain role in the pathogenesis of febrile diseases, such as familial Mediterranean fever 23 and typhoid fever. 24 However, whether gut microbiota affects the presence of fever in COVID-19 patients is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that gut microbiota plays a certain role in the pathogenesis of febrile diseases, such as familial Mediterranean fever 23 and typhoid fever. 24 However, whether gut microbiota affects the presence of fever in COVID-19 patients is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The most well-studied example is the disorder familial Mediterranean fever (FMF), a genetic autoinflammatory disorder that causes recurrent fevers and painful inflammation in the abdomen, lungs, and joints. FMF is linked to a mutation in the human MEFV (Mediterranean fever) gene, which encodes the pyrin protein, a regulator of the innate immune system (Di Ciaula et al 2020). MEFV, through its innate immune function, also controls the gut microbiome composition (Di Ciaula et al 2020).…”
Section: Host Genetic Control Of the Microbiome Impacts Health And Diseasementioning
confidence: 99%
“…FMF is linked to a mutation in the human MEFV (Mediterranean fever) gene, which encodes the pyrin protein, a regulator of the innate immune system (Di Ciaula et al 2020). MEFV, through its innate immune function, also controls the gut microbiome composition (Di Ciaula et al 2020). During times of active FMF, the gut microbiome exhibits a depletion of total numbers of bacteria, loss of diversity, and shifts in relative abundance of populations of Bacteroidetes, Firmicutes, and Proteobacteria phyla (Khachatryan et al 2008).…”
Section: Host Genetic Control Of the Microbiome Impacts Health And Diseasementioning
confidence: 99%
“…Guardia-Escote et al 101 also showed that the composition of gut microbiota in early life can be modulated by the APOE genetic background. Environmental factors such as dietary habits, living conditions, and contamination of environmental matrices can also interact with genetic profiles to affect gut microbiota composition 93 , 102 .…”
Section: Genetic and Environmental Factors Affect Gut Microbiotamentioning
confidence: 99%